Clinicopathological characteristics and outcomes of 23 patients with secretory carcinoma of major salivary glands - Jingjing Sun (Nature Portfolio, 2021)
Abstract This retrospective study investigated the clinicopathological characteristics of secretory carcinoma of salivary glands (SCSG) in 23 patients with histopathologically confirmed SCSG between January 2010 and December 2020. In total, 13 males and 10 females (ratio, 1.3:1) aged 10 − 69 years (median, 45 years) were enrolled in this study; the average disease duration was 2.44 years (0.25–20 years). Twenty-one patients (91.3%) had SCSG in the parotid gland, and two (8.7%) in the submandibular gland. All patients had single nodules of diameters 0.8–4.8 cm (average 2.6 cm); five with lymph node metastases, and two with distant metastases. Immunohistochemically, tumors stained positive for S-100, mammaglobin, CK7, GATA3 and pan-Trk, and negative for DOG1, P63, and calponin, with Ki-67 positivity from 1 to 50%. ETV6 gene rearrangement was confirmed in 15 patients. All patients underwent oncological resection, four had radioactive particles implanted postoperatively, one received chemotherapy, and seven underwent chemoradiotherapy. Six patients had regional recurrences, two distant metastases, and one died before the last follow-up. SCSGs are typically indolent, with a low locoregional recurrence rate and excellent survival. Prognosis is correlated to clinical stage, pathological grade, and surgical procedures.